The Grid Voltage's Asymmetrical Fault Detection Method based on Variable-Step LMS Adaptive Notch Filter Algorithm - Wang, Yifan; Wang, Shuhong; Zhang, Ailing; Wang, Jingxuan (IOP conference series. Earth and environmental science, 2019)
For wind turbine systems (WTS), the grid voltage fault detection algorithm determines the response speed of WTS to grid voltage fault. This paper proposed a sort of voltage asymmetrical fault detection method, to detect negative-sequence component in grid voltage, variable-step (VS) least mean square (LMS) adaptive notch filter (ANF) is applied to eliminate the 2nd-harmonic frequency component. The application of ANF can separate negative-sequence component from grid voltage, therefore the voltage asymmetrical fault can be detected; the self-tuning of controllable parameters of ANF can be realized by the LMS adaptive algorithm, which is convenient and efficient in practical application; furthermore, because the variable step size adjustment is adopted, the contradiction between convergence rate and steady-state error of ANF can be solved. The MATLAB/Simulink simulation and FFT analysis results are in conformity with the theorical analysis, which proves the feasibility of the method.